PERMBERDAYAAN EKONOMI DALAM RANGKA PENINGKATAN PENDAPATAN MASYARAKAT DESA KLAMPIS BARAT KABUPATEN BANGKALAN - Octaviana Arisinta; Ika Lis Mariatun; Manah Tarman; Aldila Septiana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Jombang), 2026)
This community service activity aims to empower micro, small, and medium enterprises (MSMEs) in West Klampis Village by improving the production quality and marketing of anchovy chili sauce products to increase community income, particularly in West Klampis Village, Bangkalan Regency. Implementation methods include outreach, training, processing, more hygienic and attractive packaging, and social media-based digital marketing strategies. Results indicate increased community understanding of safe food production standards, increased product packaging variations that better suit market needs, and increased promotional reach through digital platforms. This empowerment is expected to increase the competitiveness of local MSMEs, increase income, and contribute to sustainable village economic development